2022
DOI: 10.3389/fimmu.2022.1022380
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular traps in ischemia reperfusion injury

Abstract: In response to strong signals, several types of immune cells release extracellular traps (ETs), which are web-like structures consisting of DNA decorated with various protein substances. This process is most commonly observed in neutrophils. Over the past two decades, ET formation has been recognized as a unique mechanism of host defense and pathogen destruction. However, the role of ETs in sterile inflammation has only been studied extensively in recent years. Ischemia reperfusion injury (IRI) is a type of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 200 publications
(317 reference statements)
0
12
0
Order By: Relevance
“…In addition to capturing and killing microorganisms causing infectious diseases, NETs are also involved in the occurrence and development of non-infectious diseases, including cancer ( 28 ), autoimmune diseases ( 29 , 30 ), thrombosis ( 31 ), and sterile inflammatory tissue injury ( 32 ). Among them, renal IRI is a typical type of sterile inflammatory injury in which NETs play an important role ( 33 , 34 ). Studies have shown that inhibition of NET formation or promotion of NET degradation by PAD4 inhibitor or DNase I can improve renal IRI ( 16 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to capturing and killing microorganisms causing infectious diseases, NETs are also involved in the occurrence and development of non-infectious diseases, including cancer ( 28 ), autoimmune diseases ( 29 , 30 ), thrombosis ( 31 ), and sterile inflammatory tissue injury ( 32 ). Among them, renal IRI is a typical type of sterile inflammatory injury in which NETs play an important role ( 33 , 34 ). Studies have shown that inhibition of NET formation or promotion of NET degradation by PAD4 inhibitor or DNase I can improve renal IRI ( 16 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is gathering evidence that neutrophils deliver inflammatory molecules using a potent process that promotes IRI in many transplanted organs including the liver ( 1 ). For reasons that are not yet clear, some but not all neutrophils can expel nuclear and mitochondrial DNA fibers that are bound with inflammatory cytokines, proteolytic enzymes, and histones.…”
Section: Cc1-l Restrains Iri and Netosismentioning
confidence: 99%
“…For reasons that are not yet clear, some but not all neutrophils can expel nuclear and mitochondrial DNA fibers that are bound with inflammatory cytokines, proteolytic enzymes, and histones. These extracellular DNA fibers, known as neutrophil extracellular traps (NETs), were first reported to trap and kill pathogens ( 2 ), but can cause parenchymal tissue damage in the absence of observable infection ( 1 ). Most investigation has focused on elucidating the signals that promote NETosis.…”
Section: Cc1-l Restrains Iri and Netosismentioning
confidence: 99%
“…To date, two main forms of NETs release have been reported [2,3,[5][6][7][8][9][10][11], namely, lytic NETosis or suicidal NETosis and nonlytic NET formation or vital NET formation [6,[12][13][14][15]. Suicidal NETosis is a nicotinamide adenine dinucleotide phosphate (NADPH) oxidase-dependent death process characterized by nuclear and granular membrane disintegration, chromatin decondensation, and the release of chromatin decorated with granular proteins and cell rupture.…”
Section: Two Main Forms Of Nets Release Have Been Proposedmentioning
confidence: 99%